Repertuar wydawniczy tłoczni zakonnych — na przykładzie Drukarni Jezuickiej we Lwowie - Rusińska-Giertych, Halina (Piśmiennictwo zakonne w dobie staropolskiej, 2013)
The paper deals with the publishing repertoire of monastic printing houses in the Old Polish epoch,and more particularly with the publishing repertoire of the Jesuit Printing House in Lviv, which existedfrom 1642 to 1773. Among all Polish printing houses in Lviv, the Jesuit one stood out as being both the largest and the one having the longest tradition. It inspired cultural and academic life in both the cityitself and the entire South-Eastern region of the First Polish Republic. In the span of 130 years about 700publications were printed there, most of which were religious, the others included pedagogical, scientific,journalist and literary works together with school manuals, calendars, guides, plays, official prints, etc.Such diversity is evidence that monastic printing houses published not only works of their own choice butalso — for financial reasons — works commissioned by other religious and secular institutions or individuals, thereby producing many texts that significantly contributed to the development of Polish writing.